Trends in causes of maternal mortality in a tertiary care centre in Kerala, India - U., Sreekumari; Nair, Shilpa (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Kerala has the lowest maternal mortality ratio compared to other Indian states. But when compared to developed countries Kerala has still a long way to go. The present study aimed to analyse the causes of maternal deaths that occurred in the study setting for a period of seven years (2011-2017). Methods: Retrospective study which was conducted at SAT hospital, Govt. Medical College, Thiruvananthapuram. All maternal deaths that occurred in the study setting from January 2011 to December 2017 were found out from registers. The baseline socio demographic characteristics, gravidity, parity, cause of death were recorded using structured proforma and analyzed using SPSS software. Results: Total maternal deaths during the time period was 101. There were 66441 live births. Maternal mortality ratio for the seven-year period was 152. Majority were primigravidae (50.49%), of low socio-economic status (79.2%), rural population (81.1%) and referred from periphery after identifying complication (85.1%). Caessarean section was the commonest mode of delivery among them (43.56%). Regarding cause of death, indirect maternal deaths were more than direct deaths (50.49% versus 42.57%). Cardiac disorder was the leading indirect cause (12.87%), Post-partum hemorrhage (13.86%), Hypertensive disorders (8.91%) and Sepsis (7.9%) were the leading direct causes. Conclusions: Early referral protocols, increasing blood and blood component availability in the periphery should be reinforced. Regarding indirect causes medical boards should be constituted in tertiary care centres for prompt and efficient multidisciplinary care.